Community-Based Action Research Approaches, Environmental Conservation, Economic Development, and Ethical Tensions: Reflections on Work in Peru and India - Levitan, Joseph; Diwakar, Shikha (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
Community-based action research (CBAR) is designed to facilitate community members’ identification of challenges in their lives, as well as to collaboratively develop ways to confront those challenges. It is also designed to be an inherently ethical and justice-oriented paradigm for social change and inquiry. When working with community members in areas such as the Peruvian Andes and North India, the problems community members now identify inevitably include the effects of environmental degradation and climate change on the community, as well as challenges with economic opportunities. When engaging in collaborative action to address these challenges, tensions can arise regarding community land-usage and its economic implications. Inherently, there are ethical implications when tensions arise between different facets of community identified needs and the possible effects of solutions. In this paper, we reflect on two projects that have had ethical tensions and consider ways CBAR can transform tensions into constructive ways forward.